The ayakashi hunter's tainted bride. 1 - Yuma, Midori (Kodansha USA Publishing, LLC, 2025)
"Young, cheerful Nanao can't wait to marry her betrothed, Reito, the young lord of the Byakurenji family. But that changes one night when she is attacked by a vengeful yokai spirit--an ayakashi--leaving her scarred with the mark of a demonic curse. Her cousin Akemi seizes the chance to steal away her fiancé, but it doesn't matter. Reito now finds her repulsive, and Nanao is forced to wear a monkey mask to hide her scar and live the life of an outcast. Years later, she meets Yako, the willfull young scion of another noble family. When Nanao's mask shatters after an accident, Yako sees her face and is drawn to her beauty and great spiritual power. But there's more to the handsome young lord than meets the eye, and when Yako offers Nanao a way out of her torturous life, the new life that awaits her is filled with more mystery and intrigue than she could ever imagine..."--